Highly Efficient and Selective Adsorption of Cationic Dyes in Aqueous Media on Microporous Hyper Crosslinked Polymer with Abundant and Evenly Dispersed Sulfonic Groups. Issue 22 (9th June 2020) - Xiong, Gang; Zhang, Qian; Ren, Baoyi; You, Lixin; Ding, Fu; He, Yongke; Fan, Xiaolei; Wang, Na; Sun, Yaguang
Abstract: To significantly promote the adsorption efficiency of dyes from aqueous media, a microporous hyper‐crosslinked polymer with abundant and evenly‐dispersed sulfonic groups acted as efficient and selective sites (HCP‐1 ) was synthesized via Friedel‐Crafts alkylation reaction from a simple Schiff‐based monomer containing sulfonic groups. HCP‐1 possessed micro‐plate morphology with the thickness of about 200 nm and high specific surface area of ∼1, 111 m 2 g −1 . HCP‐1 displayed good adsorption capacities toward cationic dyes methylene blue (MB, 1, 602.2 mg g −1 ) and basic blue 7 (BB7, 496.7 mg g −1 ) at 25 °C, but no adsorption capacity to anionic dye methyl orange (MO), showing charge selectivity. The pseudo‐second‐order kinetic model and Langmuir isotherm model were suitable for the describing adsorption process. The negative Δ G 0 values and the positive Δ H 0 values indicated that adsorption was spontaneous and endothermic. HCP‐1 still maintained adsorption efficiency of above 96% during five cycles. On the whole, HCP‐1 is an efficient and promising material in the future research and application in the purification of water polluted by cationic dyes. Furthermore, this work also develops a new strategy to directly synthesize porous HCPs containing abundant and evenly‐dispersed sulfonic groups on inner surface by designing suitable organic monomers. Abstract : A microporous hyper‐crosslinked polymer with abundant and evenly‐dispersed sulfonic groups has been synthesized via direct method, which was proven to be high removal efficiency (1, 602.2 mg g −1 for MB and 496.7 mg g −1 for BB7), selectivity and recyclability absorbent for cationic dyes in water media.